Respostas hemodinâmicas na vigília e sono de mulheres hipertensas após uma sessão de Tae Kwon Do - Wanderley, Erik de Cerqueira (2019)
Introduction: Tae Kwon Do, Korean martial art with over 80 million practitioners worldwide. Cardiovascular Coma Syndrome of Hypertensive Women Purpose: To analyze the acute effect of a Tae Kwon Do of the Born Cardiovascular of hypertensive women. Methods: 23 women (60.8 ± 6 years) hypertensive, attended by the drug form, were submitted to a control session and adjusted through breathing classes. postural. Cardiovascular variables were evaluated as systemic arterial hypertension after a 24-hour period, wakefulness and outpatient radiological control after blood flow control. Results: A demonstrative analysis of Tae Kwon Do compared to control, keeping blood pressure lower by 10.5mHg for six hours after the stimulus, reducing DBP by 5.6mmHg 75min after term, as well as maintaining the frequency cardiac output at 6bpm up to four hours. In wake and sleep no differences were found between Tae Kwon Do and control. Conclusion: the behavior of blood pressure and cardiopulmonary function after the Tae Kwon Do session demonstrates that the modality can be adopted as an auxiliary form of drug control of arterial hypertension in hypertensive women.